THE INFLUENCE OF AN INCLUSIVE LEARNING ENVIRONMENT ON SOCIALIZATION AND LEARNING OF PRIMARY SCHOOL STUDENTS - Agus Hidayat; Azwar Rahmat; Al-Amin (Indonesian Journal of Education (INJOE), 2024)
Inclusive education has always been understood as an approach to learning about the differences and diversity of learners, providing equal opportunities for everyone to engage in the same learning process. The study in this research uses the literature search method. The findings of the investigation suggest that inclusive learning environments have a significant positive impact on students' social skills development. Among inclusive environments, students tend to show improvement in their ability to follow each other, cooperate and respect diversity. This not only helps in the formation of learners' individual character and values but also enhances their ability to adapt among diverse social situations. In addition, students' learning is positively influenced by an environment that supports the diversity of individual learning styles, enabling them to reach their full academic potential. This study recommends further integration of inclusive education principles in the primary school curriculum, including continuous teacher training and development of supportive resources, as a strategic step in strengthening socialization and learning processes. The implications are expected to help establish an educational ecosystem that is not only inclusive but also enriches students' learning experiences, encouraging them to become holistic, empathetic individuals who are ready to face global challenges.